141k views
0 votes
Find f-g. I do not need explanation, just an answer is fine

Find f-g. I do not need explanation, just an answer is fine-example-1
User Nhenrique
by
4.7k points

1 Answer

1 vote

In order to calculate f - g, we need to subtract the functions. To do so, we will need to put the fractions in the same denominator.

So we have:


\begin{gathered} f-g \\ =(x-1)/(x+3)-(x-3)/(x+1) \\ =((x-1)(x+1))/((x+3)(x+1))-((x-3)(x+3))/((x+1)(x+3)) \\ =(x^2-1)/((x+3)(x+1))-(x^2-9)/((x+3)(x+1))_{} \\ =(x^2-1-(x^2-9))/((x+3)(x+1)) \\ =(x^2-1-x^2+9)/((x+3)(x+1)) \\ =(8)/((x+3)(x+1)) \end{gathered}

User AvatarKava
by
4.5k points